Anthocyanins in Blueberries Grown in Hot Climate Exert Strong Antioxidant Activity and May Be Effective against Urinary Tract Bacteria - Ana B. Cerezo; Giorgiana M. Cătunescu; Mercedes Martínez-Pais González; Ruth Hornedo-Ortega; Carmen R. Pop; Crina Claudia Rusu; Flore Chirilă; Ancuța M. Rotar; M. Carmen Garcia-Parrilla; Ana M. Troncoso (MDPI AG, 2020)
Anthocyanins are extensively studied for their health-related properties, including antibacterial activity against urinary tract infections (UTI). Among common fruits, blueberries, with their remarkable antioxidant capacity, are one of the richest sources. Anthocyanin-rich extracts were obtained from four varieties: Snowchaser, Star, Stella Blue and Cristina Blue, grown in the hot climate of Southern Spain. Their total anthocyanins contents (TAC) were determined spectrophotometrically, and the anthocyanin profile by ultra high performance liquid chromatography-tandem mass spectrometer (UHPLC-MS/MS). Their antioxidant activity was assessed by oxygen radical absorbance capacity (ORAC) assay, while antibacterial activity against strains isolated from UTI patients was assessed in vitro, helping to select the varieties with the highest bioactive potential. Star showed the highest TAC and antioxidant activity (1663 ± 159 mg of cyanidin-3-O-glucoside (cy-3-O-glu) equivalents/100 g fresh weight (FW), 6345 ± 601 μmol Trolox equivalents (TE)/100 g FW, respectively), followed by Cristina Blue, Stella Blue and Snowchaser. As far as we know, this is the first time that cyanidin-3-rutinoside has been identified in blueberries. The extracts inhibited all the tested strains, MICs ranging from 0.4 mg/mL (for Stella Blue extract against UTI P. aeruginosa) to 9.5 mg/mL (for all extracts against UTI K. pneumoniae ssp. pneumoniae). This is the first study that assessed in vitro the antibacterial activity of blueberries against Klebsiella pneumoniae, Providencia stuartii and Micrococcus spp. strains isolated from UTI.